Screening the immune-related circRNAs and genes in mice of spinal cord injury by RNA sequencing - Li, Yongjin; Wang, Baobao; Sun, Wenzhi; Kong, Chao; Li, Guowang; Chen, Xiaolong; Lu, Shibao (Frontiers in Immunology, 2022)
Spinal cord injury (SCI) is a pathological condition that leading to serious nerve damage、disability and even death. Increasing evidence have revealed that circular RNAs (circRNAs) and mRNA are widely involved in the regulation of the pathological process of neurological diseases by sponging microRNAs (miRNAs). Nevertheless, the potential biological functions and regulatory mechanisms of circRNAs in the subacute stage of SCI remain unclear. We analyzed the expression and regulatory patterns of circRNAs and mRNAs in SCI mice models using RNA-sequencing and bioinformatics analysis. A total of 24 circRNAs and 372 mRNAs were identified to be differentially expressed. Then we identifying the immune-related genes (IRGs) from them. The protein-protein interaction network were constructed based on the STRING database and Cytoscape software. Furthermore, Go and KEGG enrichment analysis were conducted to predict the functions of the IRGs and host genes of DECs. These findings will contribute to elucidate the pathophysiology of SCI and provide effective therapeutic targets for SCI patients.